+0  
 
0
69
1
avatar

3(2-x)=5(2x-7)+2

Guest Jul 11, 2017
edited by Guest  Jul 11, 2017
Sort: 

1+0 Answers

 #1
avatar+815 
+2

In this equation, our goal is to isolate the unknown, x. Let's see how we would go about doing that

 

\(3(2-x)=5(2x-7)+2\) This is the original equation. Distribute the 3 and the 5 into the given parentheses.
\(6-3x=10x-35+2\) Combine -35+2.
\(6-3x=10x-33\) Add 33 to both sides,
\(39-3x=10x\) Add 3x to both sides.
\(39=13x\) Divide by 13 to isolate x. 
\(3=x\)  
   

 

There ya go!

TheXSquaredFactor  Jul 11, 2017

9 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details